Balancing cost, infection, and time to functional fistula use in hemodialysis access: single-stage vs. two-stage brachiobasilic fistula - A, Ahmad; Abd Aziz, Mohd Fahmi; Abdul Rahman, Mohd Norhisham Azmi; Othman, Ahmad Faidzal (The Editorial Committee of Annals of Vascular Diseases, 2025)
Objective: This study compares single-stage versus two-stage brachiobasilic arteriovenous fistula (BBAVF) creation for hemodialysis access, specifically examining total procedural costs, catheter-related bloodstream infection (CRBSI) rates, and time to functional fistula use. Methods: This retrospective cohort study included patients who underwent either single-stage or two-stage BBAVF creation between 2023 and 2024. Patients were grouped by procedure type, and outcome metrics such as total healthcare costs (including surgical, hospital, and follow-up costs), CRBSI incidence, and time to fistula use were analyzed. Results: The single-stage BBAVF approach was associated with significantly lower total costs compared to the two-stage approach. Costs for the single-stage procedure ranged from RM50 to RM1200, while the two-stage procedure ranged from RM930 to RM4000. The cost savings in the single-stage group were attributed to reduced surgical sessions, fewer interim catheter placements, and a shorter time to functional fistula use. In terms of CRBSI incidence, the single-stage method showed a notable reduction in infection rates, likely due to decreased dependence on temporary central venous catheters during the maturation period. This reduction in CRBSI is clinically relevant, as it reduces hospital readmissions, lowers overall morbidity, and minimizes the risks and complications associated with bloodstream infections. The average weekly admission cost for CRBSI was estimated to be around RM1500. The CRBSI rate in single-stage BBF is approximately 7.7%, whereas the rate in two-stage BBF is significantly higher at 66.7%. This stark difference indicates a markedly lower infection risk in single-stage BBF creation compared to the two-stage approach. In terms of time to fistula use, single-stage BBAVF allowed for faster access readiness, reducing the need for interim catheter use and associated complications. Conclusions: Single-stage BBAVF creation presents a costeffective alternative to the traditional two-stage approach by offering significant reductions in healthcare costs and CRBSI rates. Although the two-stage approach may offer certain procedural advantages, the reduced CRBSI incidence and total healthcare costs highlight the value of single-stage BBAVF for select patients. Clinicians should consider patient-specific factors, such as vascular anatomy, dialysis urgency, and comorbidities, to optimize clinical and economic outcomes. Future prospective studies are recommended to further validate these findings.